Transformasi Balanced Scorecard di Era AI: Integrasi Cybersecurity dan Digital Sustainability untuk Ketangguhan UMKM - Diana Putri; Slamet Slamet (MDP Student Conference, 2026)
The transition to Industry 5.0 necessitates AI adoption among Small and Medium Enterprises (SMEs), yet introduces critical vulnerabilities in cybersecurity and digital sustainability. Traditional Balanced Scorecard (BSC) frameworks are increasingly inadequate due to their reliance on lagging financial indicators and strategic blindness toward intangible digital risks. This study reconstructs the BSC by integrating cybersecurity and digital environmental metrics to enhance organizational resilience. Employing a mixed-methods approach comprising a Systematic Literature Review, Delphi technique, and comparative case studies the research formulates an "AI-Era Balanced Scorecard." Empirical results demonstrate that this predictive-adaptive framework significantly outperforms traditional models, reducing Mean Time to Response (MTTR) by 91.6% and improving energy efficiency by 18%. Furthermore, the model increased customer retention to 85% and reduced phishing vulnerability from 35% to 5%, confirming its necessity for SME sustainability in the digital economy